Transcranial alternating current stimulation for schizophrenia: a systematic review of randomized controlled studies - Wei, Xin; Shi, Zhan-Ming; Lan, Xian-Jun; Qin, Zhen-Juan; Mo, Yu; Wu, Hua-Wang; Huang, Xing-Bing; Zeng, Qing-Bin; Luo, Li-Xia; Yang, Xin-Hu; Zheng, Wei (Frontiers in Psychiatry, 2024)
Background: In randomized clinical trials (RCTs) investigating the application of transcranial alternating current stimulation (tACS) in schizophrenia, inconsistent results have been reported. The purpose of this exploratory systematic review of RCTs was to evaluate tACS as an adjunct treatment for patients with schizophrenia based on its therapeutic effects, tolerability, and potential.Methods: Our analysis included RCTs that evaluated adjunctive tACS' effectiveness, tolerability, and safety in schizophrenia patients. Three independent authors independently extracted data and synthesized it using RevMan 5.3 software.Results: Three RCTs involving 76 patients with schizophrenia were encompassed in the analysis, with 40 participants receiving active tACS and 36 receiving sham tACS. Our study revealed a significant superiority of active tACS over sham tACS in improving total psychopathology (standardized mean difference [SMD]=-0.61, 95% confidence interval [CI]: −1.12, -0.10; I 2 =16%, P=0.02) and negative psychopathology (SMD=-0.65, 95% CI: −1.11, -0.18; I 2 =0%, P=0.007) in schizophrenia. The two groups, however, showed no significant differences in positive psychopathology, general psychopathology, or auditory hallucinations (all P>0.05). Tw o RCTs examined the neurocognitive effects of tACS, yielding varied findings. Both groups demonstrated similar rates of discontinuation due to any reason and adverse events (all P>0.05).Adjunctive tACS is promising as a viable approach for mitigating total and negative psychopathology in individuals diagnosed with schizophrenia.However, to gain a more comprehensive understanding of tACS's therapeutic effects in schizophrenia, it is imperative to conduct extensive, meticulously planned, and well-documented RCTs.